The Performance-Based Budgeting Implementation: a Systematic Review of the Empirical Literature - Carrillo, Víctor; Jiménez, Adriana; Medina, Verónica; González R., Marino J. (Revista del CLAD Reforma y Democracia, 2021)
The Performance-Based Budgeting (PBB) is a management model that aims to increase efficiency and transparency of public policies by using program performance information in the budget cycle decisions. Although the literature links PBB to improvements in government performance, the available evidence reveals that progress in its implementation has been discrete. In this context, this article is the first systematic review of the empirical literature on PBB implementation that includes Latin American information sources in its search strategy. The study was carried out following the guidelines established by the “Preferred reporting items for systematic review and meta-analysis protocols” (PRISMA - P). In total, descriptive and conceptual data were extracted from 57 studies written between 1986 and 2019 resulting in the following findings: 1) the research program became progressively internationalized and sophisticated in its inquiry strategies; 2) the most relevant variables that affected PBB implementation were: the characteristics of budget laws and formats, the maturity of performance measurement systems, inter-institutional coordination, the role of the budget office, the characteristics of the population and the context of fiscal stress; 3) the PBB mainly influenced the budget decisions of the executive branch and was not a relevant instrument for the legislature; and 4) the studies recorded impacts of the PBB on: the behavior of public spending and managerial and accountability processes. Finally, the review proposes a new research agenda based on the elaboration of comparative studies between regions, the application of mathematical and statistical models, as well as the use of practical theories to produce public policy implications.